2018
DOI: 10.1038/s41598-018-27599-4
|View full text |Cite
|
Sign up to set email alerts
|

Gallic acid improves cardiac dysfunction and fibrosis in pressure overload-induced heart failure

Abstract: Gallic acid is a trihydroxybenzoic acid found in tea leaves and some plants. Here, we report the effect of gallic acid on cardiac dysfunction and fibrosis in a mouse model of pressure overload-induced heart failure and in primary rat cardiac fibroblasts, and compare the effects of gallic acid with those of drugs used in clinics. Gallic acid reduces cardiac hypertrophy, dysfunction, and fibrosis induced by transverse aortic constriction (TAC) stimuli in vivo and transforming growth factor β1 (TGF-β1) in vitro. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 40 publications
0
42
0
Order By: Relevance
“…Cardiac hypertrophy is an important characteristic of many cardiovascular diseases; it usually results in heart failure and is a major cause of mortality worldwide [1]. Cardiac hypertrophy results in myocardial adverse remodeling, which includes myocardial fibrosis, cardiomyocyte death, and cardiac dysfunction [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac hypertrophy is an important characteristic of many cardiovascular diseases; it usually results in heart failure and is a major cause of mortality worldwide [1]. Cardiac hypertrophy results in myocardial adverse remodeling, which includes myocardial fibrosis, cardiomyocyte death, and cardiac dysfunction [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…GA has been attributed a wide range of biological effects, including antioxidant, anti-inflammatory, antimicrobial, and antitumor (Farhoosh & Nyström, 2018;Rajan & Muraleedharan, 2017;Yao et al, 2017). In addition, the effect of GA on the reduction of chronic degenerative diseases such as diabetes (Abdel-Moneim, El-Twab, Yousef, Reheim, & Ashour, 2018;Abdel-Moneim, Yousef, El-Twab, Reheim, & Ashour, 2017), obesity (Huang, Chang, Yang, Wu, & Shen, 2018), heart disease (Jin, Piao et al, 2017;Jin, Sun et al, 2018), and cancer (Liao, Chen, Huang, & Wang, 2018;Sales et al, 2018) has been studied. However, GA exhibits poor stability at high temperatures, in oxygen, in light, and in alkaline pH, in addition to its low absorption after oral administration (Acevedo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This importance of this compound in cardiovascular protection has also been demonstrated in other experimental models. Jin et al [72], for example, observed that 7 also had positive effects on cardiac dysfunction and fibrosis in a mouse model of pressure overload-induced heart failure, demonstrating its potential as therapeutic agent for cardiac dysfunction and fibrosis in chronic heart failure. Jin et al…”
Section: Isolated Compounds From Brazilian Medicinal Plants With Diurmentioning
confidence: 99%